E-Service Quality Factors Impacting Customers Purchase Retention in E-Retailing in Malaysia - Azwar Mehdi Qassim Agha (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Many organizations have faced problems and challenges on furnishing online service quality to satisfy the customers. In Malaysia e-retailing is still a new business area. All Malaysians are not exposed to the online transaction over the internet and most often they are still hesitate to make online purchasing due to reasons of security, reliability and threat of fraud on transactions. Education of internet use for reliable information search and internet purchasing is also one of the main factors required to go for e-retailing. Without this technical literacy it would be very difficult for the consumers to go for online purchasing. This study designed and collected data from 148 customers who purchase online. Findings of this study indicate that “Information Quality,” “Internet Security,” “Service reliability” are the key determinants of E-Service Quality among online buyers in Malaysia. The implication for the owner-managers of the businesses in Malaysia is that they must be aware of the significance of the key E-Services Quality indicators while designing their businesses, to attract and retain customers.